A 24 A, 100 kHz transconductance amplifier with stable current output constructed at Inmetro. (December 2021) - Kyriazis, Gregory A.
Abstract: A 24 A, 100 kHz transconductance amplifier was constructed at Inmetro as part of a trilateral South American project to develop a reference system for measuring electric power. It is based on a design conceived by NIST in the 1990s where a number of precision bipolar voltage-to-current converters are paralleled. The present design version includes stable resistors in all critical circuit nodes to increase the current output stability. Short-term magnitude and phase stability of a few parts per 10 6 has been experimentally confirmed. The amplifier construction details and performance tests are described here.